Γ-Tocotrienol Prevents Oxidative Stress-Induced Telomere Shortening in Human Fibroblasts Derived from Different Aged Individuals. Issue 1 (2010) - Makpol, Suzana; Abidin, Azrina Zainal; Sairin, Khalilah; Mazlan, Musalmah; Top, Gapor Md; Ngah, Wan Zurinah Wan
Abstract : The effects of palm γ-tocotrienol (GGT) on oxidative stress-induced cellular ageing was investigated in normal human skin fibroblast cell lines derived from different age groups; young (21-year-old, YF), middle (40-year-old, MF) and old (68-year-old, OF). Fibroblast cells were treated with γ-tocotrienol for 24 hours before or after incubation with IC50 dose of H2 O2 for 2 hours. Changes in cell viability, telomere length and telomerase activity were assessed using the MTS assay (Promega, USA), Southern blot analysis and telomere repeat amplification protocol respectively. Results showed that treatment with different concentrations of γ-tocotrienol increased fibroblasts viability with optimum dose of 80 µM for YF and 40 µM for both MF and OF. At higher concentrations, γ-tocotrienol treatment caused marked decrease in cell viability with IC50 value of 200 µM (YF), 300 µM (MF) and 100 µM (OF). Exposure to H2 O2 decreased cell viability in dose dependent manner, shortened telomere length and reduced telomerase activity in all age groups. The IC50 of H2 O2 was found to be; YF (700 µM), MF (400 µM) and OF (100 µM). Results showed that viability increased significantly (p < 0.05) when cells were treated with 80 µM and 40 µM γ-tocotrienol prior or after H2 O2 -induced oxidative stress in all age groups. In YF and OF, pretreatment with γ-tocotrienol prevented shortening of telomere length and reduction in telomerase activity. In MF, telomerase activity increased while no changes in telomere length was observed. However, post-treatment of γ-tocotrienol did not exert any significant effects on telomere length and telomerase activity. Thus, these data suggest that γ-tocotrienol protects against oxidative stress-induced cellular ageing by modulating the telomere length possibly via telomerase.